2014
DOI: 10.15406/jccr.2014.01.00032
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Value of Tissue Doppler for Left Ventricular Recovery and Remodeling after Primary Percutaneous Coronary Intervention

Abstract: by acute ST-elevated myocardial infarction and were candidate for PCI. Patients with past history of IHD, patients received thrombolytic therapy, patients with valvular disease, cardiomyopathy, significant left ventricular hypertrophy, pericardial disease, or patients with abnormal ECG as, BBB, pre-excitation, AF, atrial flutter, or complete AV block, or patients underwent coronary artery bypass surgery were excluded from the study. Study design: All patients were subjected to the following: Informed consent f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…Our findings were in agreement with those of Rashid et al (23) , who found that the cutoff value for mean systolic (S) velocity was 4.83 cm/sec or more (as opposed to 4.6 cm/sec in our study) to predict the recovery of global systolic function with 100% sensitivity, 90% specificity, and accuracy of 97.5%, 100%, and 0.986 respectively.…”
Section: Conventional Echocardiography and Systolic Functionsupporting
confidence: 93%
“…Our findings were in agreement with those of Rashid et al (23) , who found that the cutoff value for mean systolic (S) velocity was 4.83 cm/sec or more (as opposed to 4.6 cm/sec in our study) to predict the recovery of global systolic function with 100% sensitivity, 90% specificity, and accuracy of 97.5%, 100%, and 0.986 respectively.…”
Section: Conventional Echocardiography and Systolic Functionsupporting
confidence: 93%
“…This finding is dis concordant with other studies. 7 , 24 , 25 This might be explained by relative angle dependency and the frame-rate limitations of TDI, different ACS presentations selected in each study, and variable degrees of LV systolic impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Rashid et al, 2014 10 examined fifty patients with STEMI, who underwent primary PCI. Echocardiography with DTI was performed for all patients at baseline and one month after PCI.…”
Section: Discussionmentioning
confidence: 99%